Evaluating of the effect of low-level laser therapy on wound healing in rabbits - Nguyen, Thi Bich Phuong; Nguyen, Ngoc Tuan; Dinh, Van Han; Nguyen, Nhu Lam; Nguyen, Thi Huong; Le, Thi Hong Hanh; Tran, Quoc Tien; Tong, Quang Cong (Tạp chí Y Dược Huế, 2024)
Background: A large number of studies have demonstrated the wound-healing effects of LLLT in vitro, in animal models, and in clinical practice. However, there are also differences in the study results, which are dose and wavelength dependent of LLLT. Objective: Evaluation of the wound healing process in experimental animals treated with low- level laser therapy in clinical and histopathology. Subjects and Methods: Prospective study on 30 rabbits, each rabbit created two full thickness of 2R = 4 cm wounds on both sides of the back: wound A (treated with LLLT, 780 nm, 3 J/cm2 with 72 s irradiation time, 1 time per day), wound B (control: no laser). Wounds are bandaged and laser irradiated once a day according to the procedure until the lesion is completely epithelialized. Wound biopsy was taken at: before treatment (D0), after 7 days (D7), after 14 days (D14) of treatment. Monitor and evaluate progress at the local wound. Results: The area and speed of wound narrowing on the side of the laser site narrowed faster than the control side (p < 0.05). The results of rabbit skin histopathology showed that the number of inflammatory cells on the laser side decreased significantly compared with the non-laser side (p(D14) < 0.05), while the number of neovascular and fibroblasts increased rapidly on the LLLT side when compared with the control side (p(D7) < 0.05). Conclusions: LLLT (780 nm, dose 3J/cm2) increased wound healing in experimental rabbit model. LLLT promotes wound narrowing, reduces inflammation, stimulates angiogenesis, and increases collagen synthesis fibroblasts